EFFECT OF OXYTOCIN MASSAGE ON HEMOGLOBIN AND HEMATOCRIT LEVELS IN POST-CESAREAN MOTHERS: A QUASI-EXPERIMENTAL STUDY - Dewi Aryanti; Sofia Februanti; Yudi Triguna; Tetet Kartilah; Saidah Rauf; Denicell P. Tetelepta; Nasywa Agniya Zahrah (International Archives of Medical Sciences and Public Health, 2026)
Post-cesarean anemia burdens low- and middle-income settings, yet oxytocin massage’s hematological effects remain underexplored. We evaluated its 48-hour impact on hemoglobin and hematocrit. Quasi-experimental pretest–posttest study at a tertiary hospital in Tasikmalaya, Indonesia (May - October 2024). Sixty-three post-cesarean mothers were allocated by ward to oxytocin massage (15 min at 12 and 48 h postpartum) plus standard care (n = 33) or standard care alone (n = 30). The 48-h blood draw preceded the second massage session to avoid peri-session effects; intraoperative blood loss was not systematically recorded. Co-primary outcomes (hemoglobin, hematocrit) were analyzed by baseline adjusted ANCOVA with Benjamini–Hochberg correction. All 63 mothers completed the study. Adjusted hemoglobin rose (+0.83 g/dL, 95% CI +0.11 to +1.56, p = 0.028, eta^2p = 0.078) and hematocrit (+3.68%, 95% CI +1.34 to +6.03, p = 0.003, eta^2p = 0.136); both survived correction. Critically, the hemoglobin gain fell below the informal MCID (˜1.0 g/dL); its lower confidence limit approached null (E-value 1.36), signaling residual unmeasured confounding. Lochia volume decreased (p < 0.001; unblinded); fundal height did not differ. Oxytocin massage may aid short-term hematological recovery, but the sub-MCID hemoglobin effect, cesarean-indication imbalance (fetal: 100% vs 39.4%), and unrecorded blood loss render findings preliminary. Adequately powered randomized trials are needed before adoption.